A test of the hierarchical model of litter decomposition - Bradford, Mark A.; Veen, G. F. Ciska; Bonis, Anne; Bradford, Ella M.; Classen, Aimee T.; Cornelissen, J. Hans C.; Crowther, Thomas W.; de Long, Jonathan R.; Freschet, Gregoire T.; Kardol, Paul; Manrubia-Freixa, Marta; Maynard, Daniel S.; et al. (Nature Ecology & Evolution, 2017)
International audience Our basic understanding of plant litter decomposition informs the assumptions underlying widely applied soil biogeochemical models, including those embedded in Earth system models. Confidence in projected carbon cycle-climate feedbacks therefore depends on accurate knowledge about the controls regulating the rate at which plant biomass is decomposed into products such as CO2. Here we test underlying assumptions of the dominant conceptual model of litter decomposition. The model posits that a primary control on the rate of decomposition at regional to global scales is climate (temperature and moisture), with the controlling effects of decomposers negligible at such broad spatial scales. Using a regional-scale litter decomposition experiment at six sites spanning from northern Sweden to southern France-and capturing both within and among site variation in putative controls-we find that contrary to predictions from the hierarchical model, decomposer (microbial) biomass strongly regulates decomposition at regional scales. Furthermore, the size of the microbial biomass dictates the absolute change in decomposition rates with changing climate variables. Our findings suggest the need for revision of the hierarchical model, with decomposers acting as both local- and broad-scale controls on litter decomposition rates, necessitating their explicit consideration in global biogeochemical models.